Medicinal plants used in the Brazilian caatinga and the therapeutic potential of secondary metabolites: a review (Research, Society and Development, 2021)
The Caatinga biome has a wide diversity and provides the population with the use of plants for medicinal purposes. The pharmaceutical industry has a great interest in researching the metabolites present in the species of this biome, in addition to scientifically proving which pathology can be treated using the species under study. Many species that are used by the population have not yet been studied. This study aimed to seek information about medicinal plants in the Caatinga, gather historical information about the species used by the population, address the main extraction methods and the classes of secondary metabolites with their respective medicinal properties. For the elaboration of this integrative review, searches were carried out from databases such as SCIELO, LILACS, PUBMED and Science direct. The articles were searched in Portuguese and English, with the majority having been published in the last 20 years. Several plant families have been described in the studies, but the family with the largest amount of species that has medicinal potential was the Fabaceae family. The way in which the plant is prepared for use varies according to the local cultural tradition, but the predominant one is infusion and maceration.